2020
DOI: 10.1371/journal.pntd.0008363
|View full text |Cite
|
Sign up to set email alerts
|

Xenodiagnosis to address key questions in visceral leishmaniasis control and elimination

Abstract: Visceral leishmaniasis (VL) remains an important public health issue worldwide causing substantial morbidity and mortality. The Indian subcontinent accounted for up to 90% of the global VL burden in the past but made significant progress during recent years and is now moving towards elimination. However, to achieve and sustain elimination of VL, knowledge gaps on infection reservoirs and transmission need to be addressed urgently. Xenodiagnosis is the most direct way for testing the infectiousness of hosts to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 88 publications
0
23
0
1
Order By: Relevance
“…Visceral leishmaniasis in the Indian subcontinent is believed to have an anthroponotic transmission cycle as there is no direct evidence that non-human hosts can transmit infection to the sandfly vector. 9 , 10 With a decreasing number of active visceral leishmaniasis cases in the community, the relative importance of other infectious groups in the transmission dynamics is increasing. 11 Both patients with post-kala-azar dermal leishmaniasis, who have skin eruptions as sequelae of treated visceral leishmaniasis, and those with HIV co-infection, who can have repeated clinical visceral leishmaniasis episodes, have been shown to be infectious to sandflies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visceral leishmaniasis in the Indian subcontinent is believed to have an anthroponotic transmission cycle as there is no direct evidence that non-human hosts can transmit infection to the sandfly vector. 9 , 10 With a decreasing number of active visceral leishmaniasis cases in the community, the relative importance of other infectious groups in the transmission dynamics is increasing. 11 Both patients with post-kala-azar dermal leishmaniasis, who have skin eruptions as sequelae of treated visceral leishmaniasis, and those with HIV co-infection, who can have repeated clinical visceral leishmaniasis episodes, have been shown to be infectious to sandflies.…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 14 Xenodiagnosis is the most direct way to determine the infectiousness of an infected host to vector sandflies and can be used to investigate the role of potential reservoir populations in the shifting ecology of L donovani transmission. 9 The aim of this study was to use xenodiagnosis to evaluate the relative infectiousness to sandflies of patients with visceral leishmaniasis or post-kala-azar dermal leishmaniasis, before and after treatment, and asymptomatic individuals, so to provide missing information about L donovani transmission dynamics for timely incorporation into the visceral leishmaniasis elimination programme in India.…”
Section: Introductionmentioning
confidence: 99%
“…Xenodiagnosis is the classical approach for quantifying transmissibility from a host to an insect species with a view to distinguish infectious from non-infectious hosts ( Singh et al., 2020 ). This method when applied can help define the characteristics of L. donovani transmission and provide key epidemiological evidence to guide the program.…”
Section: Resultsmentioning
confidence: 99%
“…It was further expanded to larger cohorts in Bangladesh wherein the infectiousness was higher in the polymorphic variant (17/21 81%) vs. macular (9/35, 35%) cases ( Mondal et al., 2019 ); similarly, a substantial proportion of VL cases (10/15, 67%) were also able to transmit to sandflies ( Mondal et al., 2019 ). Taken together, as tracking of the Leishmania parasite in sandflies provides key information regarding the infectiousness of VL and PKDL cases ( Singh et al., 2020 ), application of molecular tools could provide information regarding the reservoir competence.…”
Section: Resultsmentioning
confidence: 99%
“…A recent xenodiagnosis study on asymptomatic VL subjects in the Mediterranean basin (Molina et al, 2020) and India (Singh et al, 2020b) indicated serologically positive asymptomatic people were not the cause for ongoing transmission (Figure 3) , suggesting that there could be an alternative non-human host sustaining transmission. These models conclude that xenodiagnosis experiments and more clinical data are necessary to predict the role of asymptomatic infection, PKDL, and domestic animals as infection reservoirs on the ISC (Tiwary et al, 2017, Le Rutte et al, 2016, Singh et al, 2020a.…”
Section: Challenges Of Elimination and Possible Infection Sources On mentioning
confidence: 99%